EXPERIENCE OF OPTIMIZATION OF PRACTICALLY-ORIENTED TEACHING OF ENGLISH-SPEAKING STUDENTS AT THE DEPARTMENT OF PEDIATRIC DENTISTRY - Khmiz, T.G. (World of Medicine and Biology, 2013)
The algorithm for preparation and conduction of the "Lessons of hygiene" in organized groups of children of pre-school institutions during medical manufacturing practices "Prevention of dental disease" and the experience of its application in order to optimize the practical-oriented teaching of English-speaking students at the department of pediatric dentistry are submitted.
Keywords: English-speaking students; practically-oriented teaching; manufacturing practices "Prevention of dental disease"; hygiene lesson